Atypical Aggressive Hemangioma of Thoracic Vertebrae Associated With Thoracic Myelopathy—A Case Report and Review of the Literature - Krishna Timilsina; Sandesh Shrestha; Om Prakash Bhatta; Sushil Paudel; Rajesh Bahadur Lakhey; Rohit Kumar Pokharel (Case Reports in Orthopedics)
Aggressive thoracic hemangiomas are rare, benign tumors that extend into the spinal canal and cause neurological symptoms. Delayed diagnosis and treatment, due to a paucity of literature on optimal treatment strategies, can increase morbidity. This case report describes a 19-year-old male patient with aggressive thoracic hemangioma who presented with upper back pain and progressive weakness of the lower extremities. The patient underwent preoperative embolization and sclerotherapy, followed by decompression, posterior instrumentation, and stabilization. The final diagnosis was confirmed by biopsy, and there was a significant improvement in neurology after the surgical intervention. The diagnosis of rare lesions, such as aggressive hemangiomas, requires a high level of clinical suspicion and the assistance of imaging modalities in patients with features of compressive myelopathy. A combination of endovascular and surgical approaches can lead to optimal outcomes.